A novel supramolecular Zn(ii)-metallogel: an efficient microelectronic semiconducting device application. Issue 4 (17th January 2023) - Karmakar, Kripasindhu; Dey, Arka; Dhibar, Subhendu; Sahu, Rajib; Bhattacharjee, Subham; Karmakar, Priya; Chatterjee, Priyajit; Mondal, Aniruddha; Saha, Bidyut
Abstract : Adipic acid, used as a low molecular weight gelator to fabricate a novel supramolecular metallogel of Zn(ii )-ions in DMF medium, gives an excellent microelectronic device of a Schottky barrier diode at room temperature. Abstract : A unique strategy for the synthesis of a supramolecular metallogel employing zinc ions and adipic acid in DMF medium has been established at room temperature. Rheological analysis was used to investigate the mechanical characteristics of the supramolecular Zn(ii )-metallogel. Field emission scanning electron microscopy and transmission electron microscopy were used to analyse the hexagonal shape morphological features of the Zn(ii )-metallogel. Interestingly, the electrical conductivity is observed in the electronic device with Zn(ii )-metallogel based metal–semiconductor (MS) junctions. All aspects of the metallogel's electrical properties were investigated. The electrical conductivity of the metallogel-based thin film device was 7.38 × 10 −5 S m −1 . The synthesised Zn(ii )-metallogel based device was investigated for its semi-conductive properties, such as its Schottky barrier diode nature.